Parents' concern about their children's weight - Lampard, A.; Byrne, S.; Zubrick, Stephen; Davis, E. (Informa Healthcare, 2008)
Parents' concern about their children's weightAuthors: Amy M. Lampard a; Susan M. Byrne ab; Stephen R. Zubrick bc; Elizabeth A. Davis dAffiliations: a School of Psychology, University of Western Australia, Crawley, WA b Telethon Institute for Child Health Research, Subiaco, WA c Centre for Developmental Health, Curtin University of Technology, Subiaco, WA d Department of Endocrinology and Diabetes, Princess Margaret Hospital for Children, Subiaco, WADOI: 10.1080/17477160701832552Publication Frequency: 4 issues per yearPublished in: journal International Journal of Pediatric Obesity, Volume 3, Issue 2 2008 , pages 84 - 92Subjects: Obesity; Pediatrics & Child Health;Formats available: HTML (English) : PDF (English)Article Requests: Order Reprints : Request Permissions Purchase Article: US$35.00 - buy now buy now add to cart buy now [ show other buying options ] purchase type customer type online access payment method price Single Article Purchase Any 3 days credit card US$35.00 buy now buy now add to cart add to cart Issue Purchase Any permanent credit card US$118.25 buy now buy now add to cart add to cart IASO Members can get a discounted rate If you would like to pay in any other currency please see the purchasing help pages for more information. * Sign In Sign In * Online Sample Online SampleAbstractObjective. Firstly, to investigate the degree of concern parents feel about their children's weight (parental concern). Secondly, to identify factors that influence this concern, and to test a model of parental concern using structural equation modeling. Subjects. A total of 347 non-overweight, overweight, and obese children (aged 6-13; Mean =9.5, SD =1.8) and their parents. Methods. Children and their parents attended an assessment session during which they were weighed and measured. Parents were administered a structured interview, which included the Eating Disorder Examination, and completed the Pediatric Quality of Life Inventory (parent proxy), and the Children's Body Image Scale. Results. Eighty-two percent of parents of overweight children, and 18% of parents of obese children reported little parental concern. Higher parental concern was associated with higher child Body Mass Index, less parental underestimation of child body size, and lower child health-related quality of life. Conclusions. Interventions targeting childhood obesity should aim to optimise parental concern by reducing parents' underestimation of child body size and increasing their awareness of the effects of overweight and obesity on children's health and quality of life.Keywords: Parental concern; childhood obesity; child weight; child quality of life; perception of weight status; perception of body sizeview references (26)Bookmark with: * CiteULike * Del.icio.us * BibSonomy * Connotea * More bookmarks * What are these?